Perlindungan Konsumen dari Iklan Kosmetik Berbahaya di Indonesia - Cahya Salma Kamila; Romi Faslah (CV. ITTC INDONESIA, 2025)
Indonesia's cosmetic industry has experienced rapid growth accompanied by the proliferation of misleading cosmetic product advertisements containing hazardous substances. This study aims to analyze the effectiveness of consumer legal protection against hazardous cosmetic product advertisements and the role of related institutions in supervision and enforcement. The research employs a normative juridical method with statutory and conceptual approaches. Data were obtained through literature study of laws and regulations, scientific journals, and official BPOM reports. The findings reveal that forms of consumer rights violations include scientifically unproven claims, absence of information about hazardous substances, dishonest testimonials, and use of fake certificates. Existing legal protection remains ineffective due to weak product supervision on social media, minimal consumer education, and limited inter-agency coordination. BPOM, Kominfo, Indonesian National Police, and YLKI have strategic roles but still face implementation challenges. Consumer awareness enhancement strategies include digital campaigns, influencer collaboration, and integration of consumer literacy in education. Mass media plays an important role in public education and social supervision. The study concludes that strengthening regulations, improving inter-agency coordination, and sustainable consumer education are necessary to achieve optimal consumer protection.